2016
DOI: 10.1021/acs.analchem.6b01395
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-Based Ultrasensitive Fluorescent Probe for the Dual-Mode Imaging of Microviscosity in Living Cells

Abstract: Microviscosity changes of living cells have a far-reaching influence on diffusion and movement capacity of RNA and, more seriously, could modify RNA functions in living cells. Fluorescent rotor, whose fluorescence responds to different environmental viscosities, holds great potential for the imaging of viscosity in biosystem. Although many fluorescent rotors have been reported for viscosity, the fluorogenic rotor with ultrasensitivity for the determination of microviscosity (<10 cP) was rarely reported. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…Salen] + Cl − 在细胞内呈多亚细胞器分布(图7). 细胞内的微黏度会随着所处环境温度的降低而 升高 [19,22,37] . 使用自噬诱导剂雷帕霉素 [38] 或者血清饥饿 [29] 参考文献…”
Section: [Alsalenunclassified
“…Salen] + Cl − 在细胞内呈多亚细胞器分布(图7). 细胞内的微黏度会随着所处环境温度的降低而 升高 [19,22,37] . 使用自噬诱导剂雷帕霉素 [38] 或者血清饥饿 [29] 参考文献…”
Section: [Alsalenunclassified
“…(D) The fluorescence lifetime measurements of BODIPY 14 (3.0 μM) with different viscosities. Reproduced with permission from Li et al (2016), Copyright 2016 American Chemical Society. (E) 2,6-Functionalized BODIPY 15 as a FMR.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported a RNA-targeted BODIPY 14 as a new FMR to detect intracellular viscosity (Figure 2C; Li et al, 2016). FMR 14 showed two different maximum wavelengths at 496 and 565 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The purine derivatives have already been demonstrated as emitters in OLEDs, [18][19][20] as pH 21 sensors or even as imaging tools for cell compartments 22 and their environment. 23 Additionally, the purine derivatives are naturallike molecules that can be more easily recognized by cells. 14 During the last decade a few examples of purines bearing traditional complexing structures like crown ethers, 24 pincer forming substituents 25 and salicyl-imine side chains 22 have been reported and applied as metal ion sensors.…”
Section: Introductionmentioning
confidence: 99%